Influence of the Demographic Regions on the Environment: Features and Development Trends - TUREKULOVA, Dametken; MUKHAMBETOVA, Lyazzat; BEISENGALIYEV, Berik; ORAZBAYEVA, Kulman; SATKANOVA, Rimma; NURGALIYEVA, Zhanna (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
One of the main threats to national security is the deterioration of the demographic situation and the health of the population, including a sharp decline in the birth rate, and an increase in mortality. In this regard, sustainable demographic processes are one of the key priorities for the country's development. In this regard, the problem of demographic changes and their large-scale economic and social changes are an urgent problem. Therefore, in recent years, much attention has been paid to the problem of demographic changes and their large-scale economic, social and environmental consequences. The purpose of the study is to analyze the demographic situation in the Republic of Kazakhstan and the impact of ecology on its development.